IMPLEMENTASI KETERBUKAAN INFORMASI PUBLIK DALAM PEMBANGUNAN DESA DI KECAMATAN TANETE RILAU KABUPATEN BARRU (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The aim is to explain or describe the extent of the implementation of public information disclosure in village development in Tanete Rilau District, Barru Regency. The research method used is a qualitative research method with data collection techniques in the form of observation, interviews, documentation. This research was conducted in Tellumpanua Village, Tanete Rilau District, Barru Regency. From the communication carried out by the Tellumpanua Village Government to the community, it has been done well by conveying information to the community regarding planning, managing village funds in village development. human resources and infrastructure facilities. The disposition or attitude of the implementers is good. Furthermore, the bureaucratic structure has been implemented well because the Tellumpanua village office is required to obey the applicable rules. Keywords: Implementation, Public Information Disclosure, Village Development